IMPLEMENTASI WORKSHEET INKUIRI TERINTEGRASI KEARIFAN LOKAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Hunaepi Hunaepi; Laras Firdaus; Taufik Samsuri; Endang Susantini; Raharjo Raharjo (Bioscientist : Jurnal Ilmiah Biologi, 2020)
The purpose of this study was to assess the effectiveness of integrated local wisdom sheets for local wisdom on students' critical thinking skills. This type of pre-experimental research with the design of one groups pre-test post-test design. Samples were 18 students taken with saturated sampling technique. The instrument used was the Critical Thinking Skills Test (TKBK) with indicators: 1) interpretation; 2) analysis; 3) conclusions; 4) evaluations; 5) explanations; and 6) self-regulation. Data were analyzed descriptively and in paired sample test statistics. The results showed that the integrated inquiry wisdom local worksheet was declared effective based on the results of the N-Gain analysis with an average value of 0.65 (moderate). Indicators of interpretation and evaluation reached a percentage of 81 with a category (very high). Skills indicators explain 80 in categories (high), analysis indicators and skills conclude 60 categories (low), and the lowest percentage in self-regulation indicators reaches 37 in categories (very low). Weak skills in analyzing and making conclusions, because student self-regulation skills are low. This condition demands the need to improve self-regulation by developing cognitive monitoring through an emphasis on learning that can practice scientific curiosity skills.